Inovasi Padi (Perpustakaan Digital) Sebagai Sumber Belajar Untuk Pembelajaran Sejarah Siswa SMA - Ash-Shidiqie, Muhammad; Hastuti, Hera (Jurnal Kronologi, 2025)
This research is motivated by the lack of variety in learning resources used in history learning, where teachers rely solely on textbooks and do not provide students with access to additional learning materials. This study aims to: (1) identify the innovation process of PADI (Digital Library) as a learning resource, (2) analyze the feasibility of PADI, (3) analyze the practicality of PADI, and (4) analyze the effectiveness of PADI as a learning resource. The research method used is Research and Development (R&D) with the ADDIE development model. The implementation was carried out with class XI/F1 students at SMA N 13 Padang. The results show that: (1) PADI was designed using the WIX platform, (2) the feasibility of PADI is categorized as very feasible, with an average score of 3.83 from material experts and 3.70 from media experts, (3) the practicality of PADI is categorized as very practical, with an average score of 3.87 from teachers and 3.76 from students, (4) the effectiveness test of PADI, based on a Google Form questionnaire, showed that 78% of students strongly agreed with its effectiveness. It can be concluded that PADI (Digital Library) is feasible, practical, and effective for use in history learning in the classroom.